GAMBIR SAWIT SEMBUNG GILANG VERSI NYI M.M RUBINEM - Sutrisni; Siswati; Asep Saepudin (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2024)
Nyi Maria Mahdalena Rubinem is a professional singer from the city of Yogyakarta before 1945 and experienced her heyday in 1955-1973. Nyi Rubinem is the only singer from the city of Yogyakarta who received the title of Maestro Sinden. This is interesting to research to find out how to work on Nyi Rubinem's sinden in more depth.  The discussion in this research is focused on Nyi Rubinem's version of working on sinden in relation to conventional working on sinden norms with the aim of knowing and describing the characteristics of working on sinden and Nyi Rubinem's strengths as a singer. To solve the problems in this research, the descriptive analysis method was used, namely a research method carried out by describing the data that has been collected, then continuing with analysis of working on sindenan. The data analyzed includes: the application of lyrics to the piece, cengkok sindenan, the generation of sinden and the presentation of sinden. The results obtained from the research show that Nyi Rubinem, in working on her sindenan, has distinctive characteristics, including the crooked sindenan srambahan seleh notes 1, 2 and 5. A striking characteristic is the color of her voice which is very shrill and tends to be kêmèng, a characteristic is also found in the repetition of the sindenan Isen-isen with a feminine, feminine accent. Nyi Rubinem's strength as a singer can be seen in her total appearance, both physically and in terms of potential/skills.